INDEPENDENT VARIATION IN NATURE OF HEMAGGLUTININ AND NEURAMINIDASE ANTIGENS OF INFLUENZA VIRUS: DISTINCTIVENESS OF HEMAGGLUTININ ANTIGEN OF HONG KONG/68 VIRUS - Schulman, J. L. (1969)
Antigenic variations of the two virus-coded surface proteins of influenza virus—hemagglutinin and neuraminidase—were examined in seven strains of influenza A(2) virus (including the Hong Kong/68 strain) isolated from 1957 to 1968. Changes in the two antigens were found to occur independently in nature, resulting in new viruses which differ from older strains more with respect to one antigen than the other. The Hong Kong/68 strain is markedly different from previous A(2) strains in its hemagglutinin antigen but possesses neuraminidase indistinguishable antigenically from that of recent strains. Immunization experiments in mice provided evidence that only the neuraminidase component of an earlier A(2) strain provided protection against Hong Kong virus challenge. Segregation of hemagglutinin and neuraminidase antigens through recombination of each of the seven strains of influenza A(2) virus with A(0)/NWS virus made it possible to investigate antigenic variation of the two dissociated surface proteins independently in a common plaque assay system. Comparison of these hybrid viruses with the parent A(2) strains provided evidence that all the cross-reactivity of the Hong Kong strain with previous A(2) viruses is explicable on the basis of its similar neuraminidase component. It is proposed that the taxonomy of influenza A viruses must take into account differences in neuraminidase as well as hemagglutinin antigens.